Nasal Reconstruction in Heminasal Deficiency (Proboscis Lateralis): Two Case Reports, with Airway Reconstruction in One Case - Fischer, Helmut; Eppstein, Ron Julius; von Gregory, Henning Freiherr; Gubisch, Wolfgang (Facial Plastic Surgery, 2014)
Proboscis lateralis is a very rare congenital malformation with heminasal hypoplasia or aplasia. The affected side is represented by a trunk (proboscis) which can be positioned from the upper eyelid down to the alar base. We present two cases of proboscis lateralis, one in which we reconstructed an airway. The first case is a 16-year-old male patient who presented with heminasal aplasia. Immediately after birth, a proboscis lateralis was resected from the right upper eyelid as primary treatment elsewhere. We reconstructed the nose using costal cartilage as framework. A paramedian forehead flap was transposed to give the patient a nose with adult dimensions. We made no attempt to reconstruct an airway in this case as unilateral nasal breathing appeared adequate. The second case is a 14-year-old male patient who presented with heminasal aplasia on his right side, where a nodule-like appendix was existent with a fistula underneath. A computed tomographic scan revealed an existing hypoplastic posterior nasal airway and a complete ventilated sinus system. The fact that there was an existing posterior airway encouraged us to construct an anterior airway to create an airflow passage. Costal cartilage was taken for framework reconstruction and nasal skin was completely replaced by a paramedian forehead flap. The reconstructed airflow passage was stable.
Keywords: proboscis lateralis; airway reconstruction; heminasal deficiency; paramedian forehead flap; craniofacial anomaly